2016
DOI: 10.4236/me.2016.74053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of CEPA on FDI to Mainland China from Hong Kong

Abstract: Regional economic integration has got great achievements both in practice and theory since 1980s, which promotes the progress of the world economic liberalization. Besides the trade creation and diversion effect which had been researched widely, regional economic integration agreement also would create investment among members, and this dynamic investment effect now has been the main factor which pushes the progress of integration. Based on DID model and Gravity Model, this paper examines the influence of CEPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Medvedev (2012) showed that the preferential trade arrangements had a positively significant impact on FDI inflows of participating countries. Similarly, the mainland and Hong Kong closer economic partnership arrangement had a positive effect on attracting FDI from Hong Kong to the mainland of China (Wang 2016).…”
Section: Effect Of International Investment Agreement On Foreign Dirementioning
confidence: 90%
See 2 more Smart Citations
“…Medvedev (2012) showed that the preferential trade arrangements had a positively significant impact on FDI inflows of participating countries. Similarly, the mainland and Hong Kong closer economic partnership arrangement had a positive effect on attracting FDI from Hong Kong to the mainland of China (Wang 2016).…”
Section: Effect Of International Investment Agreement On Foreign Dirementioning
confidence: 90%
“…In light of the presence of IIAs more recent studies have focused on the relationship between the number of bilateral investment treaties and treaties with investment provisions and foreign direct investment. These studies usually suggested their strong relationship as rigorous as possible (Colen et al 2016;Desbordes and Vicard 2009;Medvedev 2012;Nguyen et al 2020;Wang 2016). Moreover, Desbordes and Vicard (2009) indicated that the BITs with the quality of political relation between signatory countries had a positive and significant effect on bilateral foreign direct investment.…”
Section: Effect Of International Investment Agreement On Foreign Dirementioning
confidence: 98%
See 1 more Smart Citation